Spintronics handbook. Volume two, Semiconductor spintronics - Tsymbal, E. Y. (Evgeny Y.); Zutic, Igor ([Place of publication not identified] : CRC Press, 2019)
The second edition offers an update on the single most comprehensive survey of the two intertwined fields of spintronics and magnetism, covering the diverse array of materials and structures, including silicon, organic semiconductors, carbon nanotubes, graphene, and engineered nanostructures. It focuses on seminal pioneering work, together with the latest in cutting-edge advances, notably extended discussion of two-dimensional materials beyond graphene, topological insulators, skyrmions, and molecular spintronics. The main sections cover physical phenomena, spin-dependent tunneling, control of spin and magnetism in semiconductors, and spin-based applications.
Volume 2. Semiconductor Spintronics Section IV. Spin Transport and Dynamics in Semiconductors 1. Spin Relaxation and Spin Dynamics in Semiconductors and Graphene Jaroslav Fabian and M. W. Wu 2. Electrical Spin Injection and Transport in SemiconductorsBerend T. Jonker 3. Spin Transport in Si and Ge: Hot Electron Injection and Detection ExperimentsIan Appelbaum 4. Tunneling Magnetoresistance, Spin-Transfer and Spinorbitronics with (Ga,Mn)AsJean Marie George, T. Huong Dang, E. Erina, T. L. Hoai Nguyen, H.-J. Drouhin, Henri Jaffrs 5. Spin Transport in Organic SemiconductorsValentin Dediu, Luis E. Hueso, and Ilaria Bergenti 6. Spin Transport in Ferromagnet/III-V Semiconductor HeterostructuresPaul A. Crowell and Scott A. Crooker 7. Spin Polarization by CurrentSergey D. Ganichev, Maxim Trushin, and John Schliemann 8. Anomalous and Spin-Injection Hall EffectsJairo Sinova, Joerg Wunderlich, and Tomas Jungwirth Section V. Magnetic Semiconductors, Oxides and Topological Insulators 9. Magnetic Semiconductors: III-V SemiconductorsCarsten Timm 10. Magnetism of Dilute OxidesJ. M. D. Coey 11. Magnetism of Complex Oxide InterfacesSatoshi Okamoto, Shuai Dong, and Elbio Dagotto 12. LaAlO3/SrTiO3: A Tale of Two MagnetismsYun-Yi Pai, Anthony Tylan-Tyler, Patrick Irvin, and Jeremy Levy 13. Electric-field Controlled MagnetismFumihiro Matsukura and Hideo Ohno 14. Topological Insulators: From Fundamentals to ApplicationsMatthew J. Gilbert and Ewelina M. Hankiewicz 15. Quantum Anomalous Hall Effect in Topological InsulatorsAbhinav Kandala, Anthony Richardella, and Nitin Samarth.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Solid State Physics; TECHNOLOGY / Material Science; SCIENCE / Physics; Spintronics; Magnetism; Magnetic semiconductors